Analysis of the Influence of Employer Branding, Organizational Commitment, and Digital Work Environment on Employee Retention in Digital-Based Companies - Alfa Santoso Budiwidjojo Putra; Muhamad Akbar; Catik Yustina Mart; Ana Fitriyatul Bilgies; Fatimah Malini Lubis; Hertya Andriani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
According to the research, the employee retention in digital-based companies has been influenced significantly by employer branding, organizational commitment, and the quality of the digital work environment. An image of a great company can not only become a source of pride but also love for the employees' hearts, which in turn will decrease their need to exit the organization. More so, loyalty to the company is strengthened when employees feel that their personal values are in line with the company's vision, mission, and work culture. Besides that, the support of a digital work environment that provides flexibility, efficiency, and easy access to technology can be a factor in spreading a more comfortable and nice work atmosphere. These results reveal that retention policies in tech companies are not only dependent on monetary aspects. Attention is also needed to pay attention to the company's reputation, the psychological relationship between individuals and the organization, and the provision of work facilities relevant to current needs. Therefore, company management needs to consistently strengthen the company's brand as an ideal workplace, foster commitment through a supportive work environment, and make continuous investments in digital infrastructure that supports productivity. With these steps, digital companies can build employee loyalty and maintain the sustainability of superior talent, the main foundation for winning the competition in the digital economy era.